Factors that determine customers acceptance of Ar Rahn financing in Selangor - Abdul Razak, Dzuljastri; Farha Nabila, Baharum (AESS Publications, 2018)
Ar Rahn is a method of providing short-term financing by pledging jewelry to the financial institution as security. It is widely used to facilitate individual consumption and small business. The use of ArRahn is gaining prominence as an alternative to money lending which charges high-interest rate and poses a burden to customers. The paper aims to determine the factors that affect customers’ acceptance on the use of ArRahn based on three variables namely concept, pricing and justice and fairness. The methodology was carried out by survey of 121 respondents in the state of Selangor. The result indicated that only pricing has significance relationship with customers’ acceptance. This result is useful to the practitioners so that they can emphasize on pricing as the main element in the marketing of Ar-Rahn to customers. The academician can benefit by conducting further research on this eminence body of knowledge.